The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s11042-019-7229-9
|View full text |Cite
|
Sign up to set email alerts
|

Fostering computational thinking through collaborative game-based learning

Abstract: Algorithms are more and more pervading our everyday life: from automatic checkouts in supermarkets and e-banking to booking a flight online. Understanding an algorithmic solution to a problem is a very relevant activity to improve end-users' involvement. To this end, adopting a meta-design approach may help to support end-users to appropriate the design skills necessary for contributing to system design, in new and engaging modalities. By acquiring Computational Thinking (CT) skills (e.g., algorithmic thinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 56 publications
1
43
0
1
Order By: Relevance
“…The latest literature shows a growing interest in CT [35], and describes the importance of CT among students and teachers in education. According to [50], CT skills can be vastly are developed through collaborative and game-based learning like TAPASPlay, which provides a playful environment.…”
Section: Fostering Ct Skills Through Game-based Learning (Gbl)mentioning
confidence: 99%
“…The latest literature shows a growing interest in CT [35], and describes the importance of CT among students and teachers in education. According to [50], CT skills can be vastly are developed through collaborative and game-based learning like TAPASPlay, which provides a playful environment.…”
Section: Fostering Ct Skills Through Game-based Learning (Gbl)mentioning
confidence: 99%
“…Students need to be able to understand how computational systems work and their value for societal issues [1] and also develop the skills to access, critically analyse and interpret data and information, recognise emerging cultural and social biases embedded in the design of computer systems, and the ethical and political implications [6,7,18]. Such skills and competences can empower students to adopt a more critical and inquisitive approach towards existing technological environments and to engage more actively in the design of new technology systems [15].…”
Section: Introductionmentioning
confidence: 99%
“…There are many approaches to promote learning CT in young children which led to popular research topics, such as block-based programming [8], robotic programming [9], unplugged activity [10], collaborative game-based learning [11], integrated into STEM [12], from STEM to STEAM [13], board game [7], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, students can learn how to solve problems effectively and foster CT skills. Several studies have shown that game-based learning can increase student motivation and improve their learning outcomes [11].…”
Section: Introductionmentioning
confidence: 99%